Is OSPAR 98/3 science-based politics or politics-based science? - Paces, Nicole; Davies, Abigail J.; Hastings, Astley (Frontiers in Marine Science, 2024)
Man-made structures in the marine environment such as offshore Oil & Gas infrastructure are known to provide a hard substrate that enables ecosystems to develop on and around them. Current decommissioning practices on the UK Continental Shelf are mandated by the OSPAR Decision 98/3 with the premise of a clean seabed at its core, meaning that it is the expectation that all infrastructure is completely removed at the end of its operation life, leaving a clear seabed behind. This study critically reviewed 49 peer-reviewed articles relating to the ecosystem and the impact to these ecosystems by current removal practices. The results clearly demonstrate that current science-based evidence shows that existing O&G platform substructures act as multipurpose artificial reefs upon which rich ecosystems have developed and that their removal degrades the overall North Sea marine environment. Furthermore, this study shows that clear-sea bed policies, such as OSPAR 98/3, do not reflect, nor understand the complex relationship and interdependencies between biology and man-made structures and do not reflect current scientific knowledge. It is concluded that based on current knowledge, it is no longer scientifically justifiable to mandate the removal of all O&G infrastructure during decommissioning and that applying the principle of a clean seabed according to the OSPAR Commission should be re-considered.